The evolution of galaxies in the context of the cosmic web - Tudorache, MN (2024)
Traditionally, studies of the cosmic web in observations are done using optical/near-infrared data. However, there is a plethora of information hidden in the other wavelengths - especially in radio. In this thesis, I discuss how observations of neutral hydrogen (HI) can be used to understand the flow of gas in the intergalactic medium and how it links to the filaments of the cosmic web. Specifically, I investigate how the filaments of the cosmic web have an effect on the spin of the filaments and the physical processes that could be involved. Additionally, I explore how star formation histories (SFHs) derived from photometric bands and spectroscopy can be used to elucidate the relationship between neutral gas fraction and spin-filament alignment. Furthermore, I investigate the utilisation of SFH-derived parameters within an HI-selected sample to establish correlations between star formation, stellar mass, and HI mass. Moreover, I delve into the use of photometric redshifts, despite their inherent uncertainties, to probe the cosmic web at higher redshifts and draw insights into their impact on galaxy properties. Lastly, I discuss preliminary findings regarding an elongated Hi structure comprising 14 dwarf galaxies discovered in the local Universe, which appears to trace the cosmic web, and its implications for models of galaxy evolution.